The Collision of Centuries of Chinese Literature and Christian Culture - ZHANG, Xiaoying (Journal of Research for Christianity in China (JRCC), 2025)
Religion and literature are two different forms of cultural phenomena, and they are related to each other and can influence and interact with each other. From a macro perspective, Christian culture has a profound influence on literary creation, especially for the development of Western literature. The spread of Christianity in China has a long history. It can be traced back to the end of the third century AD. After the accumulation and precipitation of time, Christian culture has had many influences on Chinese local culture. Although Christian cultural thought cannot become the mainstream of Chinese literature, it cannot be denied that the collision of literature and religious culture has also promoted the development of modern and contemporary Chinese literature to a certain extent.
Keywords: Chinese literature, Christian culture, Western literature